The hard line - Greaney, Mark (Greaney, Mark. Gray Man novel., 2026)
"Court Gentry's current family operates out of an office park in Norfolk, Virginia. Ghost Town is an off-the-books direct action team run by Matt Hanley, former CIA deputy director. They take on the jobs the Agency needs handled "discreetly," and those jobs are rolling in. Somewhere at the top of the US intelligence apparatus, security experts and intelligence operations worldwide are being threatened. It starts with a blown safe house in Tunis. Then Court himself barely escapes from an ambush in the jungles of Nicaragua. Now, key members of the US counterintelligence community are being assassinated in their own neighborhoods. With the feds compromised, it's up to Court and his team to stop the hit squads. But eliminating professional kill teams may be the least of the Gray Man's worries when he finds himself targeted by the legendary assassin code-named Whetstone--a man driven out of retirement by a very personal quest to rain down hellfire on Court and everyone he's ever loved, starting with the father he hasn't seen in twenty years"-- Provided by publisher.